Visualization of Droplet Dynamics in Cloud - Belgaonkar Shubham; Bamble Bhushan; Barve Amit; Kumar Bipin (ITM Web of Conferences, 2020)
Data visualization uses charts, graphs and maps to illustrate some information. Visualizing data helps us understand information faster. The study of droplet dynamics is a critical part of cloud physics and includes studying droplet properties. The aim of this work is to visualize the droplet dynamics obtained from DNS (Direct Numerical Simulation) data due to evaporation and condensation of the droplets. This simulation contains coupled Eulerian and Lagrangian frames. Animation is created for both Eulerian grid data and Lagrangian droplet movement. Scientific visualization provides a way to analyze these turbulent properties in a part of a cloud and learn about the nature of droplets and mixing process in such highly turbulent areas.